Disentangling balance impairments in spinal and bulbar muscular atrophy. (13th July 2019) - Anagnostou, E; Zachou, A; Breza, M; Kladi, A; Karadima, G; Koutsis, G
Highlights: Kennedy patients exhibit severe balance deficits in conditions of absent vision. Horizontal vestibulo-ocular reflex function is preserved. The balance impairment stems from a diminished somatosensory input. Some Kennedy patients face difficulties in producing fast eye movements. Abstract: Spinal and bulbar muscular atrophy (Kennedy's disease) has been associated with balance dysfunction and falls. However, postural control has not been studied quantitatively. Here, we quantified upright stance and aimed to disentangle the role of vestibular, proprioceptive and oculomotor deficits. Static balance was assessed in Kennedy patients (n = 7) during quiet stance on a force platform under different visual and proprioceptive feedback conditions. Vestibular function was assessed with the video head impulse test. Sural nerve neurography was employed to evaluate the severity of peripheral neuropathy. Also, horizontal saccades were recorded and quantified by the main sequence relationship. Posturographic analyses revealed significantly increased body sway, more pronounced in conditions with closed eyes, which was also reflected in the calculated Romberg indices. Horizontal vestibulo-ocular reflex gains were normal, i.e . > 0.75. In contrast, compound sensory nerve action potentials were markedly decreased in all patients (mean = 2.4 μV). Two patients showed slow saccades with increased exponential main sequence constants. We conclude that Kennedy patients exhibit severe deficits in quiet stance. Postural instability is greatest in conditions of absent vision with reduced proprioception being the main determinant of unsteadiness. Some patients show slowed saccadic eye movements suggesting a nuclear abducens neuronopathy.